Innovative Flap Reconstruction for Bed Sores: Right Inferior Gluteal Artery Perforator-Based Rotation Flap - Mohd. Altaf Mir; Jaya Jain (Key Flaps in Plastic Surgery, 2023)
This book chapter presents a case report and discussion on the management of a grade III sacral bed sore in a patient with paraplegia and a history of spinal cord injury. The patient had a non-healing ulcer in the sacral region for four months. The case presentation describes the diagnosis and the surgical procedure performed, which involved debridement and reconstruction using a right inferior gluteal artery perforator-based rotation flap. The secondary defect was grafted with a split-thickness skin graft. The postoperative period remained uneventful, and satisfactory results were observed during follow-up examinations. The discussion section provides an overview of bed sores, including risk factors, stages, prevention strategies, and treatment options. Risk factors for bed sores include immobility, poor nutrition, age, chronic medical conditions, and incontinence. Prevention strategies include regular repositioning, adequate nutrition and hydration, appropriate support surfaces, and proper skin care. Treatment options for bed sores include wound care, offloading and pressure redistribution, infection management, nutritional support, and surgical interventions. Surgical interventions may involve procedures such as debridement, flap reconstruction, or skin grafting. In the presented case, a gluteal artery perforator-based rotation flap was used to cover the sacral soft tissue defect. Complications associated with bed sores include infection, delayed wound healing, osteomyelitis, and sepsis. These complications highlight the importance of timely and appropriate management of bed sores. The abstract emphasizes the significance of early recognition and intervention in the management of bed sores. It highlights the surgical approach used in this case and provides a comprehensive overview of bed sores, including prevention strategies and treatment options. By understanding the risk factors, stages, and complications of bed sores, healthcare professionals can effectively manage and prevent this serious medical condition, ultimately improving patient outcomes.